1978
DOI: 10.1007/bf00484205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mechanisms regulating the expression of parental alleles at the GPD locus in mule erythrocytes

Abstract: Erythrocyte glucose-6-phosphate dehydrogenase (G6PD) was examined by 13% starch gel electrophoresis in 74 mules (42 females and 32 males), 35 donkeys, and ten horses. The quantitative expression of the parental alleles at the Gpd locus varies greatly in female mules from the hemizygous expression of the maternal allele to that of the paternal. The data obtained indicate that the X chromosomes are randomly inactivated in females mules. No selective advantage of a cell population with a maternally (or paternally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In 1969, Hamerton et al (1969Hamerton et al ( , 1971 reported nonrandom X inactivation in female mules, suggesting that the X inactivation might be aberrant in mules. However, subsequent studies revealed that this could be due to selection during cell culture and/or the sampling effect of random X inactivation (Mukherjee and Mukherjee 1970;Mukherjee and Milet 1972;Serov et al 1978). The whole-genome level tools now available for equids and the availability of highly purified placental tissues have enabled us to address the question of X inactivation in extra-embryonic membranes in the genus Equus.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…In 1969, Hamerton et al (1969Hamerton et al ( , 1971 reported nonrandom X inactivation in female mules, suggesting that the X inactivation might be aberrant in mules. However, subsequent studies revealed that this could be due to selection during cell culture and/or the sampling effect of random X inactivation (Mukherjee and Mukherjee 1970;Mukherjee and Milet 1972;Serov et al 1978). The whole-genome level tools now available for equids and the availability of highly purified placental tissues have enabled us to address the question of X inactivation in extra-embryonic membranes in the genus Equus.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…In the meantime, however, Serov, Zakian and Kulichkov (1978) seem to have explained the previous discrepancies with their report of red cell G6PD patterns in 32 male and 42 female mules and in 35 donkeys and 10 horses. Their findings confirmed the X linkage of G6PD as well as the differential G6PD mobility of XH and XD; the data from the large sample of female mules also indicated that random X inactivation does occur, at least in red blood cells.…”
Section: Differential Genetic Expression Of Parental Genotypes In Hybmentioning
confidence: 56%
“…In each hybrid, the X chromosome with the least amount of heterochro matin was shown, by using biochemical markers, to be (predomi nantly) nonrandomly active. In female mules, although both pa rental species (the donkey and horse) have widely different amounts of heterochromalin, random XCI was observed (Serov et al, 1978). Based on these reports, as well as our own observations, it seems likely that, rather than the amount of heterochromatin per se, specific sites or sequences within the heterochromatic regions of the X chromosome might determine which X chromosome will be inactivated.…”
Section: Discussionmentioning
confidence: 77%